Teletandem and teacher’s beliefs about culture and language: Deconstruction or reinforcement of stereotypes? - Salomão, Ana Cristina Biondo [UNESP] (IGI Global, 2019)
The present scenario of globalization and intercultural communication brings about new language learning contexts, such as Teletandem, to connect language teaching from a local and global perspective through telecollaboration. In this article, some results of a qualitative research are presented, focusing on a blended extension course for continuing education of language teachers in the Teletandem Brasil Project. The participants were eight Brazilian teachers who made regular teletandem sessions with Uruguayan and Argentinean teachers of Portuguese as a foreign language through Skype. The data analysis pointed to the need to reflect whether teletandem practice leads to deconstruction or reinforcement of beliefs about language and culture for these teachers. In this way, the results pose a challenge to mediation in Teletandem practice, which ought to address concepts of language and culture from a postmodern perspective as well as practitioners’ beliefs in order to allow the interactions to work as a context for reflection and deconstruction of stereotypes.
Keywords: Culture; Deconstruction or reinforcement of stereotypes; Language; Language learning; Mediation; Teacher education; Teacher’s beliefs; Telecollaboration; Teletandem